Legal Certainty of Case Settlement Criminal Acts After Bankcrupty Decision - Gunawan, Dedek (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The issue of legal certainty in the settlement of criminal cases after a bankruptcy decision is a complex and important issue in the Indonesian legal system. In this case, the settlement of criminal cases after a bankruptcy decision poses a challenge, due to the differences between the principles of bankruptcy and criminal law. A bankruptcy decision that results in the settlement of debt obligations through the process of asset liquidation can conflict with the settlement of criminal acts involving criminal sanctions for perpetrators of the crime. This study aims to examine the legal certainty related to the settlement of criminal cases that occur after a bankruptcy decision, as well as to analyze the role and limitations of existing laws in efforts to resolve such criminal cases. By using a normative approach and analysis of applicable laws and regulations, the results of this study are expected to provide a clear picture of the relationship between bankruptcy law and criminal law in order to ensure legal certainty for the parties involved. Legal certainty is needed so that the process of resolving criminal cases is not disrupted by bankruptcy status, and to maintain justice for both creditors and parties involved in criminal acts. In conclusion, this study suggests that there should be harmonization between bankruptcy provisions and criminal acts so that there is no legal uncertainty in resolving criminal cases after a bankruptcy decision.